Analysis of risk factors associated with cerebral angiography headache - Madeira, Tiago; Correa, Amanda Viguini Tolentino; Abranches, Gabriela de Paula; Masruha, Marcelo Rodrigues (Arquivos de Neuro-Psiquiatria, 2023)
Background Despite previous studies indicating a moderate/high incidence of angiography headache (AH), there is still limited data about the risk factors associated with its occurrence.Objective The present study aimed to assess the associations among demographic, clinical, and technical characteristics of cerebral digital subtraction angiography (DSA) and the occurrence of AH.Methods Cross-sectional analytical observational study with a sample comprised of individuals with a recommendation for elective DSA. Clinical interviews were conducted to assess the occurrence of AH, using a standardized questionnaire.Results Among 114 subjects, the mean age was 52.8 (±13.8) years old, 75.4% (86/114) were women, 29.8% (34/114) had a history of migraines, and 10.5% (12/114) had chronic headaches. The overall frequency of AH was 45.6% (52/114). Of those, 88.4% (46/52) underwent 3D angiography, 7.7% (4/52) underwent aortography, and 1.9% (1/52) underwent both procedures. There was a statistically significant association between AH and previous history of migraine (odds ratio [OR]: 4.9; 95% confidence interval [CI] 1.62–14.7; p = 0.005) and 3D angiography (OR 6.62; 95%CI: 2.04–21.5; p = 0.002).Conclusions 3D angiography is strongly associated with the occurrence of AH, which has never been reported before. The association between a previous history of migraine and AH confirms the results of previous studies.
Keywords: Cerebral Angiography; Headache; Migraine Disorders; Headache Disorders, Secondary; Headache Disorders